Findings from home‐based HIV testing and facilitated linkage after scale‐up of test and treat in rural South Africa: young people still missing. Issue 10 (27th August 2019) - Baisley, KJ; Seeley, J; Siedner, MJ; Koole, K; Matthews, P; Tanser, F; Bärnighausen, T; Smit, T; Gareta, D; Dlamini, S; Herbst, K; HM, Yapa; et al.
Abstract : Objectives: The aim of the study was to estimate rates of linkage to HIV care and antiretroviral treatment (ART) initiation after the introduction of home‐based HIV counselling and testing (HBHCT) and telephone‐facilitated support for linkage in rural South Africa. Methods: A population‐based prospective cohort study was carried out in KwaZulu Natal, South Africa. All residents aged ≥ 15 years were eligible for HBHCT. Those who tested positive and were not in care were referred for ART at one of 11 public‐sector clinics. Individuals who did not attend the clinic within 2 weeks were sent a short message service (SMS) reminder; those who had not attended after a further 2 weeks were telephoned by a nurse counsellor, to discuss concerns and encourage linkage. Kaplan–Meier methods were used to estimate the proportion of newly diagnosed individuals linking to care and initiating ART. Results: Among 38 827 individuals visited, 26% accepted HBHCT. Uptake was higher in women than in men (30% versus 20%, respectively), but similar in people aged < 30 years and ≥ 30 years (28% versus 26%, respectively). A total of 784 (8%) tested HIV positive, of whom 427 (54%) were newly diagnosed. Within 6 months, 31% of women and 18% of men < 30 years old had linked to care, and 29% and 16%, respectively, had started ART. Among those ≥ 30 years, 41% of women and 38% of men had linked to care within 6 months, and 41% and 35%, respectively, had started ART. Conclusions: Despite facilitated linkage, rates of timely linkage to care and ART initiation after HBHCT were very low, particularly among young men. Innovations are needed to provide effective HIV care and prevention interventions to young people, and thus maximize the benefits of universal test and treat.